The Synergistic Action of Laser and Photosensitizer on staphylococcus aureus Wound Infection in Mice - Thamer Mutlag Jasim (College of Pharmacy / Mustansiriyah University, 2009)
This study was designed to determine the effect of diode laser alone and in combination with cefotaxime and povidone-iodine (as photosensitize) on wound healing. Wounds (1 cm in length were induced in the backs of the mice). Wounds were infected with S. aureus. Wounded mice divided to nine groups and treated by laser (as one exposure for 0.5, 1, 2, 3 minutes each three days), cefotaxime alone, povidone iodine alone, povodine iodine and cefotaxime, povodine iodine and laser, cefotaxime and laser, and laser- cefotaxime- povodine iodine combination. Laser in combination with either povidone iodine or cefotaxime significantly accelerate wound healing compared with other groups. The best significant results were obtained with the using of laser- povidone iodine- cefotaxime combination. Laser exposure also minimizes the minimum inhibitory concentration of the antibiotic against S. aureus when it exposed to it. The best period of exposure in vivo was found to be 0.5 min once exposure each 3 days. The acceleration of wound healing induced by laser could be attributed toone or more of the following its bactericidal effect on the contaminated microorganism, its effect on the pathogenicity of these organism, changing of resistance pattern of the contaminants, or its interference with the events participated in wound healing and subsequent increase in the rate of the healing. This study proved that laser is a good therapyfor healing injuries; therefore clinical trials are required to assay its efficacy in human being.